[LB.02.02] 24-HOUR SYSTOLIC BLOOD PRESSURE IS INDEPENDENTLY ASSOCIATED WITH DIABETIC RETINOPATHY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS. (September 2017) - Turan, Y.; Turan, E.
Abstract : Objective: Diabetic retinopathy (DR) is the leading cause of blindness in adults living in developed countries. Among patients with diabetes mellitus (DM), elevated blood pressure (BP) is one of the major modifiable risk factors for the progression of DR. The aim of this study was to examine the association between DR and systemic risk factors. Figure. No caption available. Design and method: 201 patients with Type 2 DM were enrolled in the study. 109 of these patients were with DR and 92 were without DR. Demographic characteristics, levels of serum glucose, HbA1c, Hs-CRP and 24-hour ambulatory BP determined using validated devices were evaluated. Results: Age (56.7 ± 9.6 vs. 59.9 ± 8.2, P = 0.012), duration of diabetes [9.6 (range: 1–28) vs. 13.8 (range:1–32) years, P<0.01], serum glucose [143.8 (range: 54–436) vs. 229.3 (range: 58–554) mg/dL, P < 0.01], HbA1c (7.82 ± 1.7 vs. 9.17 ± 2.18 mg/dL, P < 0.01), Hs-CRP (1.02 ± 0.17 vs. 1.12 ± 0.20 mg/L, P < 0.01), 24-hour systolic BP (125.12 ± 12.9 vs. 138.01 ± 16.09 mmHg, P < 0.01) (Figure 1) and 24-hour diastolic BP (76.51 ± 8.02 vs. 79.95 ± 9.16 mmHg, P = 0.029) were significantly higher in the DR group. In multivariate analysis, higher serum glucose (OR: 1.006, CI: 1.001–1.012, P = 0.018) and 24-hour systolic BP (OR: 1.036, CI: 1.003–1.071, P < 0.001) were found to be independent predictors of DR in diabetic patients. Conclusions: Our study suggests that higher serum glucose and 24-hour systolic BP is associated independently with DR in diabetic patients.